2018
DOI: 10.3847/1538-4357/aadd9b
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic O2 Levels on Planets around F, G, K, and M Stars: Effects of Lightning-produced Catalysts in Eliminating Oxygen False Positives

Abstract: Over the last few years, a number of authors have suggested that, under certain circumstances, molecular oxygen (O2) or ozone (O3) generated by abiotic processes may accumulate to detectable concentrations in a habitable terrestrial planet’s atmosphere, producing so-called “false positives” for life. But the models have occasionally disagreed with each other, with some predicting false positives, and some not, for the same apparent set of circumstances. We show here that photochemical false positives derive ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 80 publications
3
87
0
Order By: Relevance
“…The model has also been used to determine the photochemical oxygen buildup in abiotic atmospheres (Hu et al 2012;James & Hu 2018). For the latter purpose, the model has been compared with other photochemistry model in detail and we have found good agreement (Gao et al 2015;Harman et al 2018). The photochemistry model solves the one-dimensional chemical-transport equation for 111 O, H, C, N, and S species including sulfur and sulfuric acid aerosols.…”
Section: Photochemistry Modelmentioning
confidence: 89%
See 4 more Smart Citations
“…The model has also been used to determine the photochemical oxygen buildup in abiotic atmospheres (Hu et al 2012;James & Hu 2018). For the latter purpose, the model has been compared with other photochemistry model in detail and we have found good agreement (Gao et al 2015;Harman et al 2018). The photochemistry model solves the one-dimensional chemical-transport equation for 111 O, H, C, N, and S species including sulfur and sulfuric acid aerosols.…”
Section: Photochemistry Modelmentioning
confidence: 89%
“…To simulate the effect of lightning, we adopt a terrestrial production rate of NO from lightning, 6´10 8 cm -2 s -1 (Schumann & Huntrieser 2007), which is already greater than the majority of the parameter space explored previously for N2-CO2-H2O atmospheres (Wong et al 2017;Harman et al 2018). In addition, it is found that in an atmosphere more O2-rich than Earth's atmosphere, the NO production rate from lightning can be higher, up to ~10 9 cm -2 s -1 (Harman et al 2018). We also consider this higher production rate in a sensitivity study.…”
Section: Photochemistry Modelmentioning
confidence: 99%
See 3 more Smart Citations